ANALGESIC EFFECT OF PRE-EMPTIVE ORAL NSAIDS ON POST-ENDODONTIC PAIN LEVELS IN SINGLE VISIT ENDODONTICS -A SYSTEMATIC REVIEW - Sindhu Ramesh; Sindhu Ramesh; Kavalipurapu Venkata Teja (Cumhuriyet University, 2021)
Background: Pre-emptive analgesia is an anti-nociceptive treatment which reduces the postoperative pain by preventing the processing of altered afferent input. As most of the patients present with pain preoperatively have higher levels of released local inflammatory mediators. Thus, pretreatment analgesia decreases the establishment of central sensitization, a mechanism by which spinal neurons increase their response to peripheral nociceptive impulse. Objective: This systematic review aims to compare and evaluate the postoperative pain levels and analgesic intake on preoperative oral administration of NSAIDs in single visit root canal treatment. Data Sources: The present review was done according to PRISMA guidelines and was registered in the PROSPERO (Centre for Reviews and Dissemination University of York; http://www.crd.york.ac.uk/PROSPERO). Registration number - CRD42020195775. The research question was formulated based on the PICO strategy. A comprehensive electronic literature search was conducted across PubMed/Medline, Scopus and Cochrane Database independently by two reviewers. Study Eligibility Criteria: Articles published from January 1990 to May 2019 that focused on preemptive strategies in single visit root canal treatment were included in the present review. Based on specified inclusion and exclusion criteria's, the selected articles were subjected to quality assessment, and the risk of bias was evaluated. Methods: A total of 6 articles were included, out of which three were hand searched. The overall risk of bias of included studies was moderate, and the study limitations were high. Results: Among the studies included, Ibuprofen was considered as the best drug of choice in single visit endodontics. Limitations: The present review was assessing only the effectiveness of NSAIDs in single visit root canal treatment. But ideally comprehensive literature should search on effectiveness in both single and multiple visit root canal treatments. Conclusion: The present systematic review concluded that ibuprofen was considered to be an effective drug in single visit root canal treatment.